Weight Status and Alcohol Intake Modify the Association between Vitamin D and Breast Cancer Risk. Issue 3 (27th January 2016) - Deschasaux, Mélanie; Souberbielle, Jean-Claude; Latino-Martel, Paule; Sutton, Angela; Charnaux, Nathalie; Druesne-Pecollo, Nathalie; Galan, Pilar; Hercberg, Serge; Le Clerc, Sigrid; Kesse-Guyot, Emmanuelle; Ezzedine, Khaled; Touvier, Mathilde
Abstract: Background: Mechanistic hypotheses suggest that vitamin D may contribute to the prevention of breast cancer. However, epidemiologic evidence is inconsistent, suggesting a potential effect modification by individual factors. Objective: Our objective was to perform exploratory analyses on the prospective associations between the plasma 25-hydroxyvitamin D [25(OH)D] concentration, polymorphisms of genes encoding for the vitamin D receptor ( VDR ) and vitamin D-binding protein (also known as gc-globulin or group-specific component, GC ), and breast cancer risk, along with 2 potential modifiers: body mass index (BMI; in kg/m 2 ) and alcohol intake. Methods: A nested case-control study was set up in the SUpplémentation en VItamines et Minéraux Anti-oXydants (SU.VI.MAX) cohort (1994–2007), involving 233 women with breast cancer and 466 matched controls (mean ± SD age: 49 ± 6 y). The plasma total 25(OH)D concentration and gene polymorphisms were assessed on samples obtained at baseline. Conditional logistic regression models were computed. Results: A higher plasma 25(OH)D concentration was associated with a decreased risk of breast cancer for women with a BMI < the median of 22.4 [OR quartile (Q)4 compared with Q1: 0.46; 95% CI: 0.23, 0.89; P -trend = 0.01, P -interaction = 0.002], whereas it was associated with an increased risk for women with a BMI ≥ the median (OR Q4 compared with Q1: 2.45; 95% CI: 1.13, 5.28; P -trend = 0.02, P -interaction = 0.002). A plasma 25(OH)D concentration ≥ 10 ng/mL was associated with a decreased risk of breast cancer for women with alcohol intakes ≥ the median of 7.1 g/d (OR ≥10 compared with <10 ng/mL: 0.50; 95% CI: 0.26, 0.95; P = 0.03, P -interaction = 0.03). The genetic analyses were consistent with the results observed with plasma 25(OH)D. Conclusion: In this prospective study, BMI and alcohol intake modified the association between vitamin D [plasma 25(OH)D and vitamin D-related gene polymorphisms] and breast cancer risk. These effect modifications suggest explanations for discrepancies in results of previous studies. This trial was registered at clinicaltrials.gov as NCT00272428.